Surgical approaches and management of panfacial trauma: A case report - Amalia L. Dewi; Mukhtar N. Anam; Eky Nasuri; Muhammad A. Latief (Journal of Dentomaxillofacial Science, 2021)
Objective : A panfacial fracture is a fracture that involves the mandible, maxilla , and zygomatic areas. Panfacial fractures may also be accompanied by the involvement of naso orbito-ethmoid (NOE) and frontal bone fractures. Open reduction internal fixation (ORIF) is one of the treatments for midface reconstruction. Case Report: 19-year-old female patient came with complaints of minor head injuries, Lefort 2 Fracture + Compression Orbital Fracture, Bilateral Zygoma Arcus Fracture . The patient was subjected to Open Reduction Internal Fixation(ORIF) for midface and orbital reconstruction under general anesthesia. Application of midface plate in regio zygoma sinistra , in regio zygoma dextra section, and glabella. After placing the midface plate, the wound was sutured. Results: Surgical management for panfacial trauma using Open Reduction Internal Fixation (ORIF) result in the unification of the midface bones and reestablishing facial deformity. Conclusion: The main goal of panfacial fracture management is to restore the occlusal connection so that other parts of the structure can be repaired.